Value chain financing and plantain production in Nigeria: An ex-ante approach - Mathew Paul Ojo; Adeolu B. Ayanwale (Financial Innovation, 2019)
Value chain finance (VCF) represents the aligning and structuring of finance within a value chain or as a result of its existence. Given the growing need to explore innovative approaches to rural and agricultural finance in Nigeria, such financing solutions have become imperative. However, few studies on the ex-ante impact of financing innovations exist. Therefore, to ascertain the benefits derivable from VCF, this paper analyzes the potential impact of VCF on plantain production in Nigeria. The expected benefits are estimated based on the economic surplus model, using the Dynamic Research Evaluation for Management (DREAM) software. Results from a 25-year simulation period at a 15% discount rate and an innovation cost of USD 1,300,000, show that, in the least optimistic scenario, the economy is expected to have an overall net gain (economic surplus) of USD 3256,800, with a net present value of USD 3406,880, benefit-cost ratio of 3.83, and an internal rate of return or break-even discount rate of 36.80%. These results indicate the positive impact of VCF, measured in terms of net present value and net benefit, expressed as producer and consumer surplus. This suggests VCF is a viable and beneficial financing innovation for food production in Nigeria. Finally, it is recommended that a value chain financing agency be established to make finance available to farmers to boost food production in Nigeria.
Keywords: 650; Ex-ante; Plantain; Value chain; Finance; Innovation; Production